Manufacture of continuous metal matrix composite strip reinforced by particulate materials from the semisolid processing - Filho, Antonio de Pádua Lima [UNESP]; Ueda, Bruno Katsuyoshi Silama [UNESP]; de Castro, Tales Paschoalino [UNESP]; de Oliveira, Rodrigo Alessandro Nunes [UNESP] (Trans Tech Publications, 2019)
Strip casting is a new method of producing metal matrix composites. Two-roll melt dragged processing (TRMD-ing) and single-roll melt dragged processing (SRMD-ing) methods were used to study the manufacture of 2-mm-thick composite strips by using PbSn (≈ 11.3 g/cm 3 ) eutectic alloy matrix reinforced with iron (≈ 7.86 g/cm 3 ) powder (≈ 70 μm) at a rate of 0.3 m/s. The metallic powder stored in the feed hopper (≈ 90 g) was pushed during the pouring operation of the cast alloy (≈ 4 kg) at 260 ºC on the cooling slope to produce a mixture of metallic slurry and particles to feed the nozzle to be dragged by the lower roll. Various surface defects occurred during processing, such as the failure of the powder particle to be embedded in the matrix by SRMD-ing with and without stirrer into the nozzle, and the rolling up of the strip into the nozzle by TRMD-ing. Graphite particles formed inside the α-Pb grain revealed a complicate eutectic structure in both the processing methods. The colloidal graphite used to coat the crucible, cooling slope, and nozzle could act as a nucleation agent for preferential centre segregation in the α-Pb grain. This suggests that the graphite particles functioned as nucleation points in the lead-rich α phase. Thus, another type of composite was formed in the presence of graphite particles within the lead-rich α-phase surrounded by β-Sn. An electron probe microanalysis and scanning electronic microscopy were used to investigate the composition and distribution and identify the different phases. Several types of particulate reinforcements may be added to the matrix to obtain composites for mechanical, electronic, and magnetic applications using these technologies.
Keywords: Metal matrix composites; Sn-Pb eutectic alloy composites; Strip casting